Implementation of Village Fund Management Policies in Mayasari Village, South Pamona District, Poso Regency - Kumalasari, Devi; A Sahibo, Samsu; Pariyati, Pariyati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
This study analyzes the implementation of village fund policies focused on managing village funds carried out by the Mayasari Village government, Pamona Selatan District, Poso Regency, the village fund policy has been in effect since 2015. In 2019 the amount of income in Mayasari Village was Rp. 1,490,223,904.00 sourced from the Village Fund in the amount of Rp. 894,263,000.00, Village Fund Allocation of Rp. 567,877,500.00 and the sharing of taxes and levies of Rp. 28,083,404.00. This research uses qualitative methods that are carried out through observation, interviews, and documentation. Data collection used the Edward III implementation theory. The results showed that the implementation of village fund management policies in Mayasari Village, Pamona Selatan Subdistrict, Poso Regency has been running quite well. However, there are still several things that must be considered, including communication between the village government and the BPD that must be improved, so that communication can run well. Also, the incentives given to Village Officials can be reconsidered to improve the welfare of Village Officials.